2019
DOI: 10.1111/aos.14170
|View full text |Cite
|
Sign up to set email alerts
|

Latanoprost treatment differentially affects intraocular pressure readings obtained with three different tonometers

Abstract: Purpose: To evaluate the apparent intraocular pressure (IOP) change observed after treatment with latanoprost in naive eyes of patients with primary open-angle glaucoma (POAG) or ocular hypertension (OHT) using Goldmann applanation tonometer (GAT), ocular response analyzer (ORA) and Corvis ST tonometry. Methods: Prospective observational cohort study. One eye from each of 59 newly diagnosed patients with POAG or OHT in our institution was analysed. IOP readings obtained using GAT, ORA and Corvis at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
1
0
0
Order By: Relevance
“…Similar to our results, a previous study by Sanchez-Barahona et al [ 27 ] compared the IOP reductions measured by GAT, ORA, and Corvis ST tonometry in patients with latanoprost and showed that the ocular hypotensive effect of prostaglandin analogues was different when measured using GAT or ORA compared to Corvis ST. However, they did not compare those with prostaglandin analogues and those without.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, a previous study by Sanchez-Barahona et al [ 27 ] compared the IOP reductions measured by GAT, ORA, and Corvis ST tonometry in patients with latanoprost and showed that the ocular hypotensive effect of prostaglandin analogues was different when measured using GAT or ORA compared to Corvis ST. However, they did not compare those with prostaglandin analogues and those without.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the measured increase in DA may have been because of decreased IOP with PGA therapy [98,108,118]. Similarly, Sanchez-Barahona and colleagues reported that three months of PGA therapy in treatmentnaïve POAG patients resulted in significant changes in corneal biomechanics based on significant changes in A1T (p = 0.001), A2T (p = 0.001), and DA (p = 0.0003) [119]. However, all three parameters are strongly affected by IOP, and changes may also be explained by IOP reduction with PGA therapy.…”
Section: Prostaglandin Analogues-induced Corneal Biomechanical Changesmentioning
confidence: 93%